The register of unscrupulous suppliers as a tool for protecting state interests and preventing violations in the procurement sphere - Zhagalov, R.B. (Bulletin of the Karaganda University “Law Series”, 2025)
The public procurement system represents a set of relationships directly linking state authorities and suppli ers. Integrity and reliability of contracting parties serve as key guarantees of stability in civil turnover. This, in turn, is defined as the principal objective of the public procurement system, namely, the effective manage ment of public finances and the state budget, as well as the protection of public interests. This article address es both theoretical and practical issues of civil-law liability of unfair counterparties arising within the sphere of tender relations in Kazakhstan. The purpose of the study is to identify the scope of civil-law liability of un fair suppliers in public procurement, to strengthen this liability, to emphasize the significance of the Register of Unfair Suppliers, and to develop relevant legislative proposals. The research applies a comparative analy sis of domestic and foreign legislation, supported by judicial practice, in order to achieve the stated objec tives. The study also proposes the introduction of the concept of an “unfair supplier” into the Law of the Re public of Kazakhstan “On Public Procurement” and other normative acts, as well as the integration of regis ters of unfair suppliers across procurement-related platforms. The methodological framework of the study in cludes formal-logical, analytical and synthetic, comparative-legal, general-state, statistical, and historical legal methods.